Synthesis and biological evaluation of novel amino-substituted derivatives of pyrido[2,3-d]pyrimidine as inhibitors of protein kinase CK2 - Zinchenko, A.N.; Muzychka, L.V.; Smolii, O.B.; Bdzhola, V.G.; Protopopov, M.V.; Yarmoluk, S.M. (Вiopolymers and Cell, 2017)
Aim. A search for human protein kinase CK2 inhibitors in a series of new amino-substituted pyrido[2,3-d]pyrimidine derivatives. Methods. Organic synthesis, analytical and spectral methods, molecular docking, in vitro biochemical testing. Results. Synthesis of new pyrido[2,3-d]pyrimidine derivatives with various aminogroups in positions 4 and 6 of the heterocycle was developed. Two compounds inhibiting kinase CK2 in micromolar concentrations were found among these derivatives. Conclusion. New pyrido[2,3-d]pyrimidin-7-ones containing aminogroups in positions 4 and 6 of heterocyclic system and new 4-amino-substituted pyrido[2,3-d]pyrimidin-7-amine derivatives have been synthesized. The inhibition activity of new pyrido[2,3-d]pyrimidines has been examined and the optimization modes have been suggested. Methyl-2-[(7-aminopyrido[2,3-d]pyrimidine-6-yl)amino]benzoate and N-(4-anilino-7-oxo-7,8-dihydropyrido[2,3-d]pyrimidine-6-yl)-3,4-dimethoxy- benzamide were found to inhibit protein kinase CK2 at IC50 of 6 and 19.5 μM, respectively. Мета. Пошук нових інгібіторів протеїнкінази СК2 людини в ряду нових амінозаміщених похідних піридо[2,3-d]піримідину. Методи. Органічний синтез, аналітичні та спектральні методи, молекулярний докінг, біохімічне тестування in vitro. Результати. Розроблено методи синтезу нових похідних піридо[2,3-d]піримідину з різноманітними аміногрупами в положеннях 4, 6, 7 гетероциклу. Серед синтезованих похідних піридо[2,3-d]піримідину виявлено дві сполуки, що інгібують кіназу СК2 в мікромолярних концентраціях. Висновки. Синтезовано нові піридо[2,3-d]піримідин-7-они, що містять аміногрупи в положеннях 4, 6 гетероциклічної системи, а також 4-амінозаміщені похідні піридо[2,3-d]піримідин-7-аміну. Досліджено інгібувальну активність похідних піридо[2,3-d]піримідину та запропоновано напрями хімічної оптимізації. Встановлено, що метил 2-[(7-амінопіридо[2,3-d]піримідин-4-іл)aмінo]бензоат та N-(4-aнілінo-7-oксo-7,8-дигідропіридо [2,3-d]піримідин-6-іл)-3,4-диметоксибензамід інгібують протеїнкіназу СК2 з ІС50 6 та 19,5 μМ відповідно. Цель. Поиск новых ингибиторов протеинкиназы СК2 человека в ряде новых аминозамещенных производных пиридо[2,3-d]пиримидина. Методы. Органический синтез, аналитические и спектральные методы, молекулярный докинг, биохимическое тестирование in vitro. Результаты. Разработаны методы синтеза новых производных пиридо[2,3-d]пиримидина с различными аминогруппами в положениях 4, 6, 7 гетероцикла. Среди синтезированных производных пиридо[2,3-d]пиримидина обнаружено два соединения, ингибирующие киназу СК2 в микромолярных концентрациях. Выводы. Синтезированы новые пиридо[2,3-d]пиримидин-7-оны, содержащие аминогруппы в положениях 4, 6 гетероциклической системы, а также 4-аминозамещенные производные пиридо[2,3-d]пиримидин-7-амина. Исследована ингибирующая активность производных пиридо[2,3-d]пиримидина и предложены направления химической оптимизации. Установлено, что метил-2-[(7-аминопиридо[2,3-d]пиримидин-4-ил)амин]бензоат и N-(4-анилин-7-оксо-7,8-дигидропиридо[2,3-d]пиримидин-6-ил)-3,4-диметоксибензамид ингибируют протеинкиназу СК2 с IC50 6 и 19,5 μМ соответственно.